Off-label use of teriparatide for the treatment of a vertebral burst fracture in a young patient: A case report and literature review - Tiziano Villa; Vincenzo Zottola; Carlo Mariani; Alberto Borgonovo; Luciano Redenti (Trauma Case Reports)
We describe a case of L2 vertebral burst fracture in a 40-year-old male patient without any other comorbidities due to a ground-fall from horse. Despite surgical intervention with L1-L3 spine fusion was indicated as the treatment of choice since no fracture healing was visible on CT after 40 days post trauma, a conservative off-label therapy was decided with 5-month administration of teriparatide and vitamin D‑calcium supplementation together with nocturnal pulsed electro-magnetic field. Complete fracture healing was obtained after 5 months.This is the first report of successful off-label use of teriparatide together with pulsed electro-magnetic field for the treatment of a burst vertebral fracture without surgical intervention in a young patient.